ACCUMULATION OF NUTRIENTS WITHIN RICE CROP SYSTEM UNDER ARSENIC TOXIC CONDITION: A HYDROPONIC STUDY - PRAKASH CHANDRA GUPTA; ARKABANEE MUKHERJEE; A. K. RAI (The Bioscan, 2012)
A hydroponic experiment was conducted in Directorate of Research, B.C.K.V., Mohanpur to observe the effect of arsenic concentration on accumulation of minerals within rice seedlings. Seedlings were treated with 0.6, 1.2 and 1.8 ppm arsenic (As) concentration along with full Hoagland solution (1940) for 14 days in net house condition. Our experiment result indicates that arsenic was mostly concentrated in roots and a little amount was moved to shoots, indicating that arsenic was not easily translocated to shoots of rice seedlings. Accumulation of P, K, Fe, Ca, Mg, Mn, Zn and Cu content decreased in leaves significantly with the arsenic treatments, indicating that rice seedlings are As-sensitive and As-toxicity depends on the arsenic concentration in the rooting medium. In root, accumulation of P, K and Mn decreased but accumulation of Ca and Cu increased with increasing arsenic concentration. Mg accumulation increased in root at 0.6 ppm arsenic concentration and decreasing in root at high arsenic concentration (1.2ppm and 1.8ppm). Fe and Zn accumulation increased with increasing arsenic concentration and at high concentration of arsenic (1.8ppm) accumulation of Fe and Zn decreased.